Acupuncture and Moxibustion for the Treatment of Gastric Pain from Theory, Method, Formula, Acupuncture Point and Technique - Yuan, Yixin; Yang, Yueqing (Journal of Contemporary Medical Practice, 2025)
Acupuncture and moxibustion is the basis of acupuncture and moxibustion treatment, and is also the specific application of the theory, method, formula, points and techniques in acupuncture and moxibustion clinic. The theoretical study of modern acupuncture evidence-based treatment lags behind clinical practice, and the process of evidence-based treatment is neglected in the clinical process, applying the mode of thinking based on specific acupuncture points, and the lack of acupuncture evidence-based treatment thinking, which restricts the development of acupuncture. The purpose of this paper is to emphasise the necessity and importance of evidence-based thinking in the treatment of gastric pain with acupuncture through the five aspects of theory, method, formula, point and technique, so as to better guide the clinical practice.